2007
DOI: 10.1007/s00192-007-0405-x
|View full text |Cite|
|
Sign up to set email alerts
|

Anterior vaginal wall length and degree of anterior compartment prolapse seen on dynamic MRI

Abstract: The objective of the study was to determine the relationship between midsagittal vaginal wall geometric parameters and the degree of anterior vaginal prolapse. We have previously presented data indicating that about half of anterior wall descent can be explained by the degree of apical descent present (Summers et al., Am J Obstet Gynecol, 194:1438−1443, 2006. This led us to examine whether other midsagittal vaginal geometric parameters are associated with anterior wall descent. Magnetic resonance (MR) scans of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 27 publications
8
53
0
2
Order By: Relevance
“…In all women, AVL was reduced after surgery and on average, AVL was shortened by 2.5 cm. Mean postoperative AVL was 6.4± 0.8 cm, similar to the mean AVL in women with normal pelvic support (6.1±1.3 cm, p=0.15) [5]. Women with longer preoperative AVLs underwent greater change in AVL (2.9 vs 1.4 cm, p=0.005; R 2 =0.78, p=<0.0001; Table 2).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In all women, AVL was reduced after surgery and on average, AVL was shortened by 2.5 cm. Mean postoperative AVL was 6.4± 0.8 cm, similar to the mean AVL in women with normal pelvic support (6.1±1.3 cm, p=0.15) [5]. Women with longer preoperative AVLs underwent greater change in AVL (2.9 vs 1.4 cm, p=0.005; R 2 =0.78, p=<0.0001; Table 2).…”
Section: Resultssupporting
confidence: 65%
“…Hsu et al showed that although apical descent is the primary factor contributing to cystocele size, increasing vaginal length accounted for 30 % of anterior wall prolapse. Re-analysis of Hsu's data found that the AVL is 23 % longer in women with cystocele than in normal controls (7.4±1.7 cm vs 6.1±1.3 cm) [5].…”
Section: Introductionmentioning
confidence: 92%
“…All United States regions, hospital types, and hospital sizes were represented in the population (Table 3). 7 The database contained a total of 6,499,132 diagnosed cases of cystocele/rectocele, apical defect, or cystocele/rectocele plus apical defect. Of those diagnosed cases, There was a significant decrease in the frequency of isolated cystocele/rectocele repair procedures performed between 1979 (96.3%, n=150,980) and 2009 (67.7%, n=61,444).…”
Section: Resultsmentioning
confidence: 99%
“…(4,5) The literature over the last 15 years advocates for a change in practice patterns, encouraging surgeons to not only recognize the role of apical defects in pelvic organ prolapse, but to also perform concomitant procedures addressing those defects. (5)(6)(7)(8)(9) In 2010 Jones and colleagues 5 used the National Hospital Discharge Survey to describe a decrease in age-adjusted rates of inpatient prolapse procedures from 1979 to 2006, especially in patients less than 52 years of age. Interestingly, a secondary outcome of their study showed an increase in apical suspension procedures in patients greater than 52 years of age suggesting that practice patterns were reflecting the movement in favor of apical support.…”
Section: Introductionmentioning
confidence: 99%
“…Summers et al showed that level-I defects contribute to the onset of cystocele, and suggested that levels I and II should be treated together to achieve efficient anterior compartment repair [18]. Yousuf et al and Hsu et al, comparing cystocele graded on POP-Q and anatomic lesions assessed on MRI, found a correlation between high-grade cystocele on MRI and cervical ring defects [19,20].…”
Section: Discussionmentioning
confidence: 99%